If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7-3(x+1)=x+3(x-1)
We move all terms to the left:
7-3(x+1)-(x+3(x-1))=0
We multiply parentheses
-3x-(x+3(x-1))-3+7=0
We calculate terms in parentheses: -(x+3(x-1)), so:We add all the numbers together, and all the variables
x+3(x-1)
We multiply parentheses
x+3x-3
We add all the numbers together, and all the variables
4x-3
Back to the equation:
-(4x-3)
-3x-(4x-3)+4=0
We get rid of parentheses
-3x-4x+3+4=0
We add all the numbers together, and all the variables
-7x+7=0
We move all terms containing x to the left, all other terms to the right
-7x=-7
x=-7/-7
x=1
| h/6=2/24 | | 8u=5u+30 | | (14x-70)=112 | | 8x-2=x+11 | | 1/4x-2=9+1/8x | | -8=4m+2 | | x^2+.75=80 | | |k/9+1/3|=12 | | 15+16x-7=4x-2-1x | | -9x•3=135 | | 212x+380=48x | | -0.20p+0.4=-1.2 | | 4+1+x=35 | | 4+1+4+5+x=35 | | 380+212x=48 | | 4x=6/8 | | 14x-3(3x-3)=4x+13 | | 6c+84=20 | | 10(4x+3)=310 | | 2+38=-5(2x-8) | | 2x-5+2x+11+2x=360 | | -8e+-19=53 | | 6w+18=42 | | c9=-11 | | 4/128=x/24 | | y-17=-5 | | 2x+11+2x=180 | | 9x2-100=0 | | 8−9k+10k−11= | | 2y=2y+11 | | X+(x-20)+(x+89)=180 | | 3x-8=4x+20 |